2023
DOI: 10.3390/ma16134837
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Zeolites from Coal Fly Ash Using Alkaline Fusion and Its Applications in Removing Heavy Metals

Abstract: The article presents studies of the influence of parameters of synthesis modes and alkali concentration on the synthesis of zeolite materials from coal fly ash (CFA). The purpose of the study was to synthesise zeolite materials from CFA using the method of alkaline fusion and to determine the susceptibility of selected heavy-metal ions to removal from solutions in an ion exchange process on a selected mesoporous zeolite. It was found that the crystalline phase of sodalite was dominated in all of the samples sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…This has become a hot area of research for the development of materials with precisely controlled pores and volume distribution. Recent studies [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] have focused more on precise control of pore shapes, sizes, and volumes to produce high-performance porous materials. The formation of pores in a material can introduce striking features into the material due to its specific surface-to-volume ratio.…”
Section: A Review Of the Contributions In This Issuementioning
confidence: 99%
“…This has become a hot area of research for the development of materials with precisely controlled pores and volume distribution. Recent studies [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] have focused more on precise control of pore shapes, sizes, and volumes to produce high-performance porous materials. The formation of pores in a material can introduce striking features into the material due to its specific surface-to-volume ratio.…”
Section: A Review Of the Contributions In This Issuementioning
confidence: 99%
“…Alternatively, alkali fusion, often with auxiliary substances like NaOH, CaCO 3 , or NH 4 F, converts insoluble crystalline phases into soluble compounds for subsequent silica extraction [7,12,13] . NaOH utilization in alkali‐fusion has yielded various zeolite phases, including sodalite, analcime, cancrinite, and Na−A (LTA) zeolites [14–16] . It is important to note that aluminium, co‐present in the liquid phase, can be separated from silica by adjusting pH [17–19] …”
Section: Introductionmentioning
confidence: 99%
“…[7,12,13] NaOH utilization in alkali-fusion has yielded various zeolite phases, including sodalite, analcime, cancrinite, and NaÀ A (LTA) zeolites. [14][15][16] It is important to note that aluminium, co-present in the liquid phase, can be separated from silica by adjusting pH. [17][18][19] The resulting silicate solution serves as the silica source for synthesizing porous materials, with templates such as CTAB (cetyltrimethylammonium bromide), P123 (Pluronic-123), and others often employed in the synthesis process.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Al-Zboon et al [ 81 ] and Huang et al [ 82 ] modified the chemical properties of CFA with sodium hydroxide and the results revealed its enhanced adsorption properties due to chemical modification. Other CFA-based materials tested to increase the adsorption capacity of CFA include modified zeolites, CFA/C HNCPs, TiO 2 /CFA, ZnO/CFA, CFA-decorated with tungsten oxide-graphene oxide, Mg(OH) 2 /calcined CFA nanocomposite and polyethyleneimine (PEI)/CFA [ 4 , 12 , 45 , 75 , [83] , [84] , [85] , [86] ]. For examples, Tauanov et al [ 85 ] and Mofulatsi et al [ 86 ] have also used a manganese coated zeolite to adsorb Cu (II) and Pb (II) ions and showed that the coating makes the adsorbent more efficient.…”
Section: Introductionmentioning
confidence: 99%